Ten-year progress of coronary artery lesions prior to Behçet disease diagnosis: A case report and care-compliant article. Issue 49 (December 2017) - Ma, Wenfang; Liang, Yan; Zhu, Jun
Abstract: Introduction: Behçet disease is a multisystemic chronic inflammatory disorder characterized by recurrent oral aphthous ulcers, genital ulcers, uveitis, and skin lesions. However, particularly part of patients would present cardiovascular involvements and vascular lesions could be the presenting sign of Behçet disease preceding classical symptoms. We presented a middle aged male patient, in whom abdominal aorta pseudoaneurysm was as the first leading sign to reveal Behçet disease, and with his coronary artery lesions progress through a 10-year period before Behçet disease was diagnosed. Conclusions: Coronary artery involvement of Behçet disease warrants more attention and investigation; repeated in-stent stenosis, aggressive progress, and elevated inflammation markers should be regard with more care earlier in clinical practice. Abstract : Supplemental Digital Content is available in the text